Comparison of the GLIM criteria with specific screening tool for diagnosing malnutrition in hospitalized patients with cirrhosis: A descriptive cross‐sectional study. Issue 2 (29th October 2022) - Yang, Wanting; Guo, Gaoyue; Mao, Lihong; Hui, Yangyang; Wang, Xiaoyu; Yu, Zihan; Sun, Mingyu; Li, Yifan; Fan, Xiaofei; Cui, Binxin; Jiang, Kui; Sun, Chao
Abstract: Background: The Global Leadership Initiative on Malnutrition (GLIM) has been built to diagnose malnutrition; however, its validity among patients with cirrhosis remains enigmatic. We aimed to investigate the prevalence of malnutrition according to GLIM criteria and compare the differences by using a specific screening tool. Methods: We conducted a descriptive cross‐sectional study analyzing hospitalized patients. The Royal Free Hospital‐Nutritional Prioritizing Tool (RFH‐NPT) was chosen as the screening tool. Estimated prevalence was shown with and without the initial screening process. Diverse combinations of phenotypic and etiologic criteria and distinct body mass index (BMI) cutoffs were applied to detect frequency of malnourished patients with cirrhosis. Results: Overall, 363 patients were recruited (median age, 64 years; 51.2% female). The prevalence of malnutrition according to GLIM criteria with and without RFH‐NPT screening was 33.3% and 36.4%, respectively. Low BMI and inflammation represented the most prevalent combination resulting in a malnutrition diagnosis (42.4%), followed by low BMI and reduced food intake (39.4%). By contrast, the least prevalence was found when combining reduced muscle mass with inflammation to diagnose malnutrition. Furthermore, the frequency of malnourished and well‐nourished participants was not statistically different when using divergent BMI reference values across the study population. Conclusions: GLIM criteria may serve a specific proxy to diagnose malnutrition, along with RFH‐NPT screening. Relevant investigation is required to report on the applied combination of phenotypic/etiologic criteria, taking into consideration the marked impact of different models. More attempts are warranted to delineate the prognostic role of GLIM criteria in the context of cirrhosis.